PC.122 Feeding practice in Extreme low Birth weight babies in a tertiary neonatal centre. (9th June 2014) - Palanisami, B; Mahaveer, A
Abstract : Background: With survival rates for preterm infants improving constantly, more emphasis is being placed on optimising nutrition. Suboptimal nutrition in the early neonatal period contributes significantly to postnatal malnutrition and accumulation of growth deficits. Delaying the introduction of enteral nutrition can result in reduced resistance to infection. Aim: To analyse the feeding practice in less than 30 weeks gestation babies in a tertiary neonatal centre. Methods: Retrospective analysis of data from July to December 2012. Data was collected from electronic patient management system (Badger) and patient notes. Results: 18/34 babies case notes were identified and analysed.15 were extreme preterm babies (<28 weeks) and 5 were more than 28 weeks. Average weight was 854 grams (range: 538–1266 grams). In first 2 weeks of life EBM was used in 16 babies and formula was used in one and feed was not started in one. Feeds were started between 2 to 8 days of life in 17 babies and on average on day 5 of life, 6 babies were fully fed by 14 days of life (range: 10–14 days). At the time of discharge from hospital 6 babies were on breast milk, 4 babies on mixed feeds, 7 babies on formula milk, and 1 baby died. Conclusion: Our unit is EBM friendly unit with 16 out of the 18 eligible babies were given EBM. But there was no EBM available from 48 h of birth as recommended by the toolkit. More education and awareness is planned to improve this.